The Notion of Presence in the Poetics of Yves Bonnefoy - John T. Naughton (Studies in 20th & 21st Century Literature, 1989)
The notion of presence is the cornerstone of Bonnefoy's entire poetics, the common element linking his earliest pronouncements about poetry to his latest. The insistence on presence emerges as the animating principle of a selfconsciously anti-Mallarmean concept of poetry that seeks to align itself with hopefulness and with an affirmation of this life. The term is never defined once and for all, however, and the great range of evocations and applications of the idea in Bonnefoy's work has triggered a significant critical debate about its significance and validity.
Keywords: presence; Yves Bonnefoy; poetics; poetry; anti-Mallarmean; self-consciousness